Analysis of the Impact of the Implementation of PSAK 115 on the Financial Performance of Real Estate Companies Listed on the Indonesian Stock Exchange - Fauziah Amalia Handayani; Djeni Indrajati Widjaja (Devotion : Journal of Research and Community Service, 2026)
The study aims to analyze the effects of the Debt-to-Asset Ratio (DAR), Current Ratio (CR), and Sales Growth on the financial performance of real estate companies and to examine the moderating role of the implementation of PSAK 115 in these relationships. This study employs a quantitative approach using secondary data obtained from the financial statements of real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The analysis was conducted using panel data regression with a moderation model to examine the direct effects of financial variables and the interaction effect of PSAK 115 implementation on companies’ financial performance. The results indicate that the Debt-to-Asset Ratio (DAR) has a negative and significant effect on financial performance, suggesting that a higher level of leverage may reduce a company’s ability to generate profits. Conversely, the Current Ratio (CR) has a positive and significant effect on financial performance, indicating that strong liquidity conditions can support operational effectiveness. Furthermore, Sales Growth demonstrates a positive relationship with profitability and contributes to improved company financial performance. The moderation test results reveal that the implementation of PSAK 115 significantly moderates the relationship between financial variables and company performance. These findings highlight that capital structure, liquidity, and sales growth are critical factors influencing the financial performance of real estate companies.